Conservation and Development of The Treasury of Cultural Information for Ang Sila Traditional Market Community, Chonburi province - Thali, Kowit (Asian Creative Architecture, Art and Design, 2022)
The research of Conservation and Development of The Treasury of Cultural Information for Ang Sila Traditional Market Community, Chonburi has the objectives following this; 1) to study the factors influencing the elements and qualifications for the cultural treasury of Ang Sila traditional market community 2) to design the cultural treasury information of Ang Sila traditional market community, Chonburi province, enhancing the cultural knowledge and 3) to develop the cultural treasury information of Ang Sila traditional market community, Chonburi province as public and accessible knowledge information. Moreover, the scope of the research is to study the wisdom and culture in the local administrative extension - Muang Ang Sila municipality, Chonburi where raises four districts; Ang Sila, Ban Puek, Some part of Huai Kapi, and some part of Samed for enhancing the cultural treasury information of Ang Sila traditional market community both intangible cultural heritage and tangible cultural heritage. The mixed methods were used as a methodology for R4 and D3 model development. It is applied for studying the research of Conservation and Development of The Treasury of Cultural information where influences the learning and people can access equally. This also is the co-knowledge sharing system for Ang Sila community. The result found that factors that affect the composition and qualification of cultural treasury information of traditional market Ang Sila community consisted of 3 components: 1) the knowledge sources of the community, 2) the process of knowledge management 3) storage and publicity. The researcher used the factors to develop a model for cultural treasury which is a high possibility, showing the reflection of this research objective that the treasury of cultural information of traditional market Ang Sila community can influence the learning and people can access equally is at high possible.